Lipodystrophy among HIV-Infected Patients Attending Care and Treatment Clinics in Dar es Salaam - Marina Njelekela; Rose Mpembeni; Alfa Muhihi; Nzovu Ulenga; Eric Aris; Deodatus Kakoko (AIDS Research and Treatment)
Background. HIV infection and long-term HAART use are associated with metabolic and morphological changes. We assessed prevalence, types, and risk factors associated with lipodystrophy among HIV-infected adults attending CTC in Dar es Salaam, Tanzania. Methods. Analysis included 466 HIV-infected patients. Study protocol involved administration of structured questionnaire to collect sociodemographic and clinical information. Diagnosis of lipodystrophy was based on physician clinical assessment. Results. Lipodystrophy was present in 95 (20.4%) of the study participants, with lipoatrophy being the most common (49.5%) followed by mixed lipodystrophy (37.9%), and lipohypertrophy was the least prevalent (12.6%). Male gender, older age, long duration on HAART, and use of Stavudine containing regimen were associated with lipodystrophy (all p<0.05). The risk for lipodystrophy was 1.6 times (AOR = 1.66, 95% CI = 1.01–2.72) for male participants and 13.3 times (AOR = 13.3, 95% CI = 6.4–27.7) for those on HAART. Long duration on HAART and use of Stavudine containing regimen were also associated with increased risk for lipodystrophy. Lipodystrophy was associated with poor perception about own body image and decreased social interactions. Conclusions. Lipodystrophy is common among HIV-infected patients in Tanzania, especially among male patients and those on HAART. Regular screening, monitoring, and patient awareness are needed for early identification and appropriate management.